Effect of antioxidants on the stability of ONO-1301, a novel long-acting prostacyclin agonist, loaded in PLGA microspheres. (May 2013) - Uchida, Takahiro; Hazekawa, Mai; Morisaki, Tomomi; Yoshida, Miyako; Sakai, Yoshiki
<x xml:space="preserve">Abstract</x> The purpose of this study was to investigate the physicochemical stability of ONO-1301 in poly(lactide-co-glycolide) microspheres (PLGA MS) under storage for 28 days in the absence or presence of butylated hydroxytoluene (BHT) or α-tocopherol as antioxidant. First, we observed the hydrolysed product: (i) in acidic solution and oxidized product and (ii) in PLGA MS under storage in HPLC study, each structure was determined by liquid chromatography–nuclear magnetic resonance/mass spectrometry. Second, ONO-1301-loaded PLGA MS containing 10% BHT was shown to be superior to ONO-1301-loaded PLGA MS without BHT, in the standpoint of the stability under storage or in vitro drug-release test, and AUC0–28 following subcutaneous injection in rats. Finally, ONO-1301-loaded PLGA MS with 10% BHT were demonstrated to be significantly more effective than ONO-1301-loaded PLGA MS without BHT in a murine sponge model of angiogenesis. In conclusion, BHT is an effective antioxidant on the stability of ONO-1301 in PLGA MS under storage.